Dual agonist/antagonist modulation of α9-containing nicotinic acetylcholine receptors by 2-ammoniumethyl ethers of stilbenol and stilbenol analogues - Giraudo, Alessandro; Tae, Han-Shen; Hung, Andrew; Richter, Katrin; Shivankar, Bhavana; Armano, Edoardo; Grau, Veronika; Pallavicini, Marco; Adams, David J.; Bolchi, Cristiano (Journal of Medicinal Chemistry, 2025)
2-(Cyclohexyldimethylammoniumethyl)ether of 4-stilbenol (2), and its styryl-modified analogues 21 and 22, were identified as lead compounds from a series targeting human alpha 9 alpha 10, alpha 9, and alpha 7 nicotinic acetylcholine receptors (nAChRs). Compounds 2 and 21 exhibited potent, and subtype-selective modulation of alpha 9-containing receptors, with low nanomolar IC50 values and dual agonist/antagonist activity in a concentration-dependent manner. In contrast, compound 22 acted as a selective, pure antagonist. Molecular dynamics (MD) simulations of compound 21 supported a concentration-dependent allosteric mechanism, with orthosteric binding at low concentrations and vestibular site interaction at higher levels. In a human monocytic cell line, all three compounds inhibited ATP-induced IL-1 beta release at nanomolar concentrations. These findings identify alpha 9 alpha 10-selective ligands as promising scaffolds for the development of nonopioid analgesics and immunomodulators, with favorable selectivity over alpha 7 nAChRs to minimize CNS-related side effects.